Rhythm disturbances in childhood obstructive sleep apnea during apnea-hypopnea episodes - Anant Khositseth; Jittamas Chokechuleekorn; Teeradej Kuptanon; Anchalee Leejakpai (Wolters Kluwer Medknow Publications, 2013)
Background: Obstructive sleep apnoea (OSA) can result in cardiovascular complications. Nocturnal arrhythmias are reported up to 50% of adult OSA patients. Arrhythmias and heart rate variability in children with OSA have not been well studied. Aims: We sought to study rhythm disturbances in childhood OSA and also to analyze the relationship of heart rate variability to the severity of OSA in children. Methods: In a retrospective cross sectional study, records of children aged < 15 years with history of snoring and suspected OSA, who had undergone polysomnography (PSG) for first time were analyzed. The cardiac rhythm and heart rate variability were studied during PSG. Results: A total of 124 patients diagnosed with OSA were grouped into mild ( n = 52), moderate ( n = 30), and severe ( n = 42) OSA. During PSG, all had sinus arrhythmias and only three patients had premature atrial contractions (PACs). The standard deviation of heart rate (SD-HR) during rapid eye movement (REM) sleep in severe OSA (9.1 ± 2.4) was significantly higher than SD-HR in mild OSA (7.5 ± 1.3, P < 0.0001). The maximum heart rate (max-HR) during REM-sleep in severe OSA (132.1 ± 22.1) was significantly higher than the max-HR in mild OSA (121.3 ± 12.6 bpm, P = 0.016). Conclusions: There was no significant arrhythmia in children with OSA during their sleep. Heart rate variability correlated with the severity of OSA.